Management Attitudes Towards Fringe Benefits - Robinson, T.H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1959)
SummaryThe author proposes (1) to define the terms « attitude » and « management »; (2) to consider some of the influences which have affected management attitudes generally; (3) to outline a few of the factors which have contributed to the growth of fringe benefits in recent years; and (4) to examine some of the factors determining the nature of management's attitudes towards fringe benefits.